Mempelajari Karakteristik Berbagai Grade Buncis (Phaseolus Vulgaris L) Varietas Lokal selama Penyimpanan Dingin 7 Hari - Kelik Putranto (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2020)
Beans (Phaseolus vulgaris L) is one type of Indonesian vegetable which is classified into non-climacteric vegetables and is very popular, in its consumption generally processed into soup. Storage of fresh beans in polyethylene plastic bags (PE) in cold temperatures is expected to prevent damage to beans during the market. However, the quality of beans after harvest varies according to grade level (diameter size), these differences can each lead to different characteristics of beans. In this study, it will be studied how the characteristics of various levels of beans when stored in cold temperatures (approximately 10oC) for 7 days storage. The purpose of this study is to get the right grade of beans (diameter size) so that during cold storage, its characteristics can be maintained. This research was conducted at the Laboratory of Food Technology at the Faculty of Agriculture, Ma’soem University. The bean varieties used are the local variety "Beunter Leuleus" from farmers in Lembang District, West Bandung Regency. Observation of the characteristics of water content, total dissolved solids, total acid content, color and texture of beans at various grade levels is done after the beans are stored for 7 days at cold temperatures (approximately 10oC). The results showed that beans with grade 0 (diameter ? 4.8mm) and grade 1 (diameter> 4.8 - 5.8) when stored in cold temperatures (10oC) for 7 days still had the preferred color and texture characteristics with water content ranged from 90.15- 90.38%, total dissolved solids were 8.70 obrix and total acid was 0.31%.